Klimageschichtliche Forschung in China: Quellenlage und Ergebnisse im Überblick - Jiaqi, Chen; King, Lorenz; Tong, Jiang; Wollesen, Dirk (ERDKUNDE, 1998)
Paleoclimatic research has a long tradition in China. Intensive studies of the historical climate have started already in the twenties of this century. These archive studies have been intensified again in the sixties and especially in the eighties due to the discussion of global climatic change. The applied research methods and selected results obtained by 60 years of historical climatic studies are presented. The main results have been obtained by the evaluation and interpretation of a large number of comprehensive climatic records in historical archives. Everywhere in China additional results come from studies in archeology, palynology and dendrochronology, as well as from the stratigraphical analysis of dust precipitation. The most important and new aspects of this research concern the calculation and presentation of paleoclimatic temperature cycles and fluctuations and the elaboration of spatial distribution patterns for flood and drought for the last 500 years. Paleoclimatic research gets much attention and support in China and its role for planning of flood protection measures is well accepted by the authorities.